A checklist of Foraminifera of the Eastern Shelf of the Adriatic Sea - Ćosović, Vlasta; Zavodnik, Dušan; Borčić, Adriana; Vidović, Jelena; Deak, Sandra; Moro, Alan (Zootaxa, 2011)
The updated and annotated checklist includes all literature records of foraminiferal species from the Eastern Adriatic coastal region and their geographic occurrences. A total of 599 recent (altogether 693 named and unidentified species) foraminiferal species were reported, classified into 232 genera according to the Lee et al. (2000) and Loeblich and Tappan (1987) classification system. In the Northern Adriatic, 536 species grouped into 211 genera are recorded, in the Central Adriatic 153 genera and 296 species are found, and in the Southern part, 272 species within 133 genera are reported. The number of lessepsian species colonizing the coasts is relatively low, implying that a) indigenous species are good competitors, and b) abiotic conditions like water temperature and substrate are unfavorable.